2020
DOI: 10.2147/clep.s199349
|View full text |Cite
|
Sign up to set email alerts
|

<p>Subsequent Development of Epithelial Ovarian Cancer After Ovarian Surgery for Benign Ovarian Tumor: A Population-Based Cohort Study</p>

Abstract: The goal of the current study is to determine the risk of subsequent development of epithelial ovarian cancer (EOC) in women after ovarian surgery for benign ovarian tumors. Patients and Methods: We conducted the nationwide population-based historic cohort study using the National Health Insurance Research Database (NHIRD) of Taiwan. Eleven thousand six hundred twenty women who underwent ovarian surgery for ovarian benign diseases were analyzed. The collected data included age, types of ovarian surgery, medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 117 publications
(211 reference statements)
0
7
0
Order By: Relevance
“…82,86 Although in Taiwan, DPP-4 inhibitors (DPP-4i) effect on the bone health in T2DM patients seemed to be supported by largescale population-based study as shown by Dr. Chang's group, 56 and additionally, DPP-4 has been extensively reviewed to provide the possible benefits on bone and subcutaneous tissue (extracelluar matrix), which are key factors of bone health. 89,90 Similar to many large-scale population-based studies, 31,56,63,[83][84][85][86][91][92][93][94][95][96][97][98] many biases, which cannot be totally excluded, may decrease the reliability and reproducibility of the data analysis. Additionally, DPP-4i may increase the risk of cholecystitis in randomized controlled trials, especially with longer treatment duration, 99 although the population-based cohort study did not support the current use of DPP-4i was associated with an increased risk of bile duct and gallbladder disease compared with current use of at least 2 oral ADA (adjusted HR, 0.99; 95% CI, 0.75-1.32).…”
Section: Antidiabetic Agents and Bonementioning
confidence: 99%
“…82,86 Although in Taiwan, DPP-4 inhibitors (DPP-4i) effect on the bone health in T2DM patients seemed to be supported by largescale population-based study as shown by Dr. Chang's group, 56 and additionally, DPP-4 has been extensively reviewed to provide the possible benefits on bone and subcutaneous tissue (extracelluar matrix), which are key factors of bone health. 89,90 Similar to many large-scale population-based studies, 31,56,63,[83][84][85][86][91][92][93][94][95][96][97][98] many biases, which cannot be totally excluded, may decrease the reliability and reproducibility of the data analysis. Additionally, DPP-4i may increase the risk of cholecystitis in randomized controlled trials, especially with longer treatment duration, 99 although the population-based cohort study did not support the current use of DPP-4i was associated with an increased risk of bile duct and gallbladder disease compared with current use of at least 2 oral ADA (adjusted HR, 0.99; 95% CI, 0.75-1.32).…”
Section: Antidiabetic Agents and Bonementioning
confidence: 99%
“…Therefore, identification of risk factors associated with progression of COVID-19 is urgently important, since early prevention and prompt management of this vulnerable population may delay or ameliorate either severity or progression of disease, which has been found in the management of various clinical conditions, regardless of life-threatening diseases or not. [75][76][77][78][79][80] Based on report from CDC in United States, 11 there are many risk factors associated with more worse pregnancy outcome in pregnant women with COVID-19 compared with age-matched nonpregnant women with COVID-19, including nonwhite ethnicity (Hispanic or Latina with RR 2.4, 95% CI, 1.3%-4.3%; Asia, nonHispanic with RR 1.4, 95% CI, 0.7%-2.7%), and presence of underlying health condition (diabetes with RR 1.5, 95% CI, 0.6%-3.5% and cardiovascular disease with RR 2.2, 95% CI, 1.0%-4.8%). While compared with pregnant women with COVID-19 who do not have the following risk factors, these pregnant women with COVID-19 who have any one of the following risk factors have faced more severe and/ 48 Huntley et al performed a systematic review and meta-analysis to compare the risk of perinatal and neonatal death among pregnant women with and without COVID-19.…”
Section: Increased Untoward Pregnancy Outcomes In Women With Co-morbi...mentioning
confidence: 99%
“…Therefore, identification of risk factors associated with progression of COVID-19 is urgently important, since early prevention and prompt management of this vulnerable population may delay or ameliorate either severity or progression of disease, which has been found in the management of various clinical conditions, regardless of life-threatening diseases or not. 75–80…”
Section: Increased Untoward Pregnancy Outcomes In Women With Co-morbi...mentioning
confidence: 99%
“… 6 However, some of them may not respond to conservative treatment well or some of them might be complicated with endometriosis-related severe complications, such as ureter stricture and reduced capacity of reproductive performance, contributing to the need of more invasive procedures, such as operations. 7 , 8 Ovarian endometrioma might be one of the most diagnosed endometrioses, which can be successfully managed by surgical approach with a relatively low risk of surgery-related complications. 7 …”
mentioning
confidence: 99%
“… 7 , 8 Ovarian endometrioma might be one of the most diagnosed endometrioses, which can be successfully managed by surgical approach with a relatively low risk of surgery-related complications. 7 …”
mentioning
confidence: 99%